2012
DOI: 10.1038/ajg.2012.135
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Cap-Assisted Colonoscopy in Polyp Detection and Cecal Intubation: A Meta-Analysis of Randomized Controlled Trials

Abstract: CAC demonstrated marginal benefit over SC for polyp detection and shortened the cecal intubation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
83
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 37 publications
5
83
2
Order By: Relevance
“…Adenoma detection has been shown to be an independent predictor of the risk of interval colorectal cancer after screening colonoscopy [5]. Several types of new technology have therefore been developed to improve adenoma detection, including high-definition white-light colonoscopy, pan-chromoendoscopy, wide-angle colonoscopy, virtual chromoendoscopy, third-eye retroscopy (TER), and cap-assisted colonoscopy (CAC) [6].CAC is a simple method in which a transparent or nontransparent rubber cap is attached to the tip of a colonoscope with an appropriate protrusion length. The cap can be readily equipped and the field of vision is not substantially affected by the cap.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Adenoma detection has been shown to be an independent predictor of the risk of interval colorectal cancer after screening colonoscopy [5]. Several types of new technology have therefore been developed to improve adenoma detection, including high-definition white-light colonoscopy, pan-chromoendoscopy, wide-angle colonoscopy, virtual chromoendoscopy, third-eye retroscopy (TER), and cap-assisted colonoscopy (CAC) [6].CAC is a simple method in which a transparent or nontransparent rubber cap is attached to the tip of a colonoscope with an appropriate protrusion length. The cap can be readily equipped and the field of vision is not substantially affected by the cap.…”
mentioning
confidence: 99%
“…CAC can help depress semilunar folds, thereby reducing the blind mucosal surface area, and may improve the efficiency of adenoma detection [6]. A study of lesions missed at colonoscopy but detected by computed tomography colonography revealed that 67 % lie on the proximal side of semilunar folds [11].…”
mentioning
confidence: 99%
See 3 more Smart Citations